New methods of local medical treatment of purulent wounds - A. Yu. Grigoryan; A. I. Bezhin; T. A. Pankrusheva; L. V. Zhilyaeva (Исследования и практика в медицине, 2020)
Purpose of the study. To study experimental model of purulent wounds efficiency of the combined effects of benzalkonium chloride and metronidazole immobilized on various bases.Materials and methods. The material was in vitro studies and experimental animals (Wistar rats), which was modeled a purulent wound and then divided into 3 groups according to the treatment method with the three studied combinations, each of which contained benzalkonium chloride and metronidazole, the combinations differed in bases, which were polyethylene oxide or sodium salt of carboxymethylcellulose, or polymethylsiloxane polyhydrate. Research methods: in an in vitro experiment, growth retardation zones were determined for the most common pathogens of wound infection using the standard disc method. In an in vivo experiment the healing process was evaluated by Popov's planimetric method, the contamination of the wounds was studied by sowing the biopsy of wounds on nutrient media with subsequent counting of the grown up colonies. The data were processed statistically, the reliability of the differences was assessed by the Kruskal-Wallis test.Results. All test combinations showed high growth retardation areas for all test strains of microorganisms. Objectively, the highest results were observed with a combination of polyethylene oxide (Staphylococcus aureus 30 (29; 30), Bacillus cereus 27 (27; 28), Escherichia coli 20.5 (20; 21), Proteus vulgaris 21.5 (20; 22), Pseudomonas aeruginosa 17 (16; 17), Candida albicans 25.5 (25; 26)). In determining the healing rate, it was noted that the maximum values in the groups when using combinations based on the sodium salt of carboxymethylcellulose and polymethylsiloxane polyhydrate occurred on day 1–3 (29.6 (27.6; 31) and 20.2 (18.8; 24.2) mm2/day, respectively), and in the group using a combination on polyethylene oxide — for 3–5 days (20.6 (17.3; 22.8) mm2/day).Conclusion. Our studies have shown the high antimicrobial activity of all the developed combinations for all the strains of microorganisms studied. It is also possible to recommend combinations on polyethylene oxide and sodium salt of carboxymethylcellulose for further preclinical studies at all times of treatment, and a combination based on polymethylsiloxane polyhydrate only in the first phase of the wound process.